(untitled) (Eventum: A Journal of Medieval Arts & Rituals, 2023)
Focusing on the late fourth-century travel account produced by a woman known today as Egeria, this article asks how her somatic, interpersonal, and sensory experiences and feelings shaped her understanding of time, or temporality. The various ways she experiences time in both parts of her diary are considered: her descriptions of travels to holy places and people in Palestine, Egypt, Syria, and Mesopotamia, followed by a detailed description of Jerusalem’s Lenten, Holy Week, and Easter rites. Taken together, the two parts of Egeria’s travel diary reveal diverse ways of measuring and feeling time. It is argued that her feelings – frustrations, excitement, joys, and sorrows – shape her experiences of the biblical past, whether through its availability or grief at its loss. The itinerarium and liturgy provide many ways to engage biblical time, whether topographically, liturgically, or calendrically.